Characterization of Mukah-Balingian and Merit-Pila Coals before and after Subcritical CO2 Exposure Using Surface-Area Techniques - Abunowara, M. (American Society of Civil Engineers (ASCE), 2020)
Carbon dioxide sequestration in unminable coal bed seams has been proposed as an option to mitigate the excessive emissions of carbon dioxide (CO2) from burning fossil fuels (coal, crude oil fractions, and natural gas) and increase natural gas production. Through laboratory experiments on CO2 adsorption using a volumetric technique, the effects of subcritical CO2 on coal structure were studied to investigate any alteration of coal textural properties induced after CO2 exposure at low pressure. Coal samples were obtained from the Mukah-Balingian and Merit-Pila coal mines of Sarawak, Malaysia. Adsorption and desorption behaviors of CO2 on dry coals were investigated utilizing a volumetric technique at 273-318 K and pressures up to 99 kPa. Brunauer-Emmett-Teller (BET) surface areas for the adsorption isotherms of N2 at the temperature of 77 K and P/Po=0.1-0.3 (where P is equilibrium pressure and Po is the saturation vapor pressure of the adsorbate) were determined for the micropores present in the coal matrix. The results of N2 adsorption and desorption isotherms are found to be represented by the Type III equilibrium adsorption, showing a formation of the unlimited multilayer. The CO2 adsorption and desorption isotherms of the four coal samples were not identical. Thus, positive hysteresis was observed between adsorption and desorption of CO2 on all coal samples. The results showed that the CO2 adsorption capacity increases with increases in micropore surface area of the samples and pressure, and it is reduced by an increase in the temperature. Interestingly, meso- and micropore characteristics of the coal samples were only slightly altered after CO2 subcritical exposure. The Langmuir isotherm model presented the best fit with the experimental data. This confirms that the CO2 molecules occupied the surface of the coal sample uniformly and created a monolayer. Â© 2020 American Society of Civil Engineers.